Histology of intestinal villi and epithelial cells in chickens fed low protein or low fat diets - Hisaya Gotoh; Tomoki Erikawa; Koh-en Yamauchi; Tossaporn Incharoen (Italian Journal of Animal Science, 2010)
To establish the intestinal histological alterations in chickens fed low crude protein (CP) or low crude fat (EE) in long-term isocaloric diets, 60 birds were allotted to three treatments, each with five replicates of four chickens. They were fed the control, low-CP, or low-EE diet from the age of 9 to 16 weeks. The chickens receiving the low-CP diet showed a clear reduction in performance and carcass characteristics like breast and wings. However, these adverse effects did not occur in the chickens fed the low-EE diet. The villus height in the duodenum and ileum were lower (P<0.05) in the low-CP group. The duodenal villus area decreased (P<0.05) in both the low-CP and low-EE groups, whereas the ileum showed a lower value (P<0.05) in only the low-CP group. The cell area of the duodenum and jejunum displayed decreasing values (P<0.05) in the low-CP and low-EE groups. As regards the mitotic numbers, the jejunum and ileum showed a decrease (P<0.05) in the low-CP group. On the villus tip surface in the duodenum of the control and low-EE groups, clear protuberant cells and cell clusters with a great number of epithelial cells were found. These cell clusters degraded to faintly dome-shaped cells in the low-CP group, resulting in a lower level of morphological changes than in the other two groups. The epithelial cells on the jejunal and ileal tip surfaces did not show a specific change in the treatment groups.